Cell-free translation of murine coronavirus RNA. - Leibowitz, J L (1982)
The coding assignments of the intracellular murine hepatitis virus-specific subgenomic RNA species and murine hepatitis virion RNA have been investigated by cell-free translation. The six murine hepatitis virus-specific subgenomic RNAs were partially purified by agarose gel electrophoresis and translated in an mRNA-dependent rabbit reticulocyte lysate, and the cell-free translation products were characterized by gel electrophoresis, immunoprecipitation, and tryptic peptide mapping. These studies have shown that RNA 7 codes for the nucleocapsid protein, RNA 6 codes for the E1 protein, RNA 3 codes for the E2 protein, and RNA 2 codes for a 35,000-dalton nonstructural protein. Genomic RNA directs the cell-free synthesis of three structurally related polypeptides of greater than 200,000 in molecular weight.